PERLAKUAN AKUNTANSI TERHADAP PEMBIAYAAN MURABAHAH - Agustinar Agustinar (Al Mashaadir : Jurnal Ilmu Syariah, 2021)
This research was also conducted in order to obtain answers to the problem "How is the accounting treatment of murabahah financing?, What is the accounting treatment for murabahah financing at PT. BPRS Adeco Langsa has complied with PSAK No.59? ”. The research method used is a qualitative descriptive method, which is to collect the data obtained then interpret and analyze it so that it can provide information that can be used to solve the problems at hand. The data used are primary data and secondary data. Based on the research conducted, it was found that PT. BPRS Adeco Langsa in recording murabahah financing refers to PSAK No.59 and murabahah accounting treatment at PT. BPRS Adeco Langsa is basically in accordance with PSAK No.59. Based on the above conclusions, PT. BPRS Adeco Langsa has implemented the provisions contained in PSAK No.59. The researcher only wants to give advice to continue to improve its financing performance, especially for murabahah financing so as to improve customer welfare.